Impact Of Corporate Governance On Firm Performance: Panel Data Evidence From Top 100 Bursa Malaysia Listed Companies - Teh, Beverly Boon Gaik (2022)
The objective of this research was to investigate the relationship between corporate governance and firm performance. Analysing 2013 to 2019 data from 81 Bursa Malaysia listed companies ranked as the Minority Shareholders’ Watchdog Group’s Top 100 Companies for Overall CG & Performance in 2019, evidence that corporate governance, in compliance with the Malaysian Code on Corporate Governance (MCCG), has a significant relationship with firm performance. Corporate governance was represented by 6 independent variables i.e., CEO duality (CDUAL), board size (BSIZE), board independence (BIND), number of board meetings (BMEET), number of women directors (WOMD), and number of directors with foreign qualifications (FORD). Firm performance was represented by earnings per share (EPS), Tobin’s Q (TOBQ), and return on equity (ROE). The descriptive analysis showed that compliance towards the MCCG is almost complete, with only two exceptions i.e., CDUAL and WOMD. Only 1 in 81 companies were found to practice CDUAL in 2019. Average percentage of women directors over the 7-year period was 18%, almost half of the 30% recommended by MCCG. Female representation on the board has improved since the last decade. The panel data analysis indicated a significant negative relationship between CDUAL, BSIZE, BIND, and BMEET, and firm performance whereas a significant positive relationship between WOMD and FORD, and firm performance was detected. This study contributes to existing literature on adoption of corporate governance practices in accordance to MCCG. It also provides insights to the government, policymakers, and various stakeholders regarding current corporate governance landscape, and how it plays a part in improving firm performance.